2017
DOI: 10.1002/nbm.3858
|View full text |Cite
|
Sign up to set email alerts
|

Renal parenchyma impairment characterization in partial unilateral ureteral obstruction in mice with intravoxel incoherent motion‐MRI

Abstract: Ureteropelvic junction obstruction constitutes a major cause of progressive pediatric renal disease. The biological mechanisms underlying the renal response to obstruction can be investigated using a clinically relevant mouse model of partial unilateral ureteral obstruction (pUUO). Renal function and kidney morphology data can be evaluated using renal ultrasound, scintigraphy and uro-magnetic resonance imaging (uro-MRI), but these methods are poorly linked to histological change and not all are quantitative. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…During the MRI scanning process, this study used free breathing mode for image acquisition, and motion artifacts inevitably exist in this study. This is consistent with what has been mentioned in previous related animal-level studies (Pons et al, 2018), and there is no better way to avoid motion artifacts at the animal level. In addition, VX2 liver tumor was inoculated in the background of normal liver, and then the liver cancer was treated with TACE, and liver fibrosis finally occurred after TACE treatment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…During the MRI scanning process, this study used free breathing mode for image acquisition, and motion artifacts inevitably exist in this study. This is consistent with what has been mentioned in previous related animal-level studies (Pons et al, 2018), and there is no better way to avoid motion artifacts at the animal level. In addition, VX2 liver tumor was inoculated in the background of normal liver, and then the liver cancer was treated with TACE, and liver fibrosis finally occurred after TACE treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Previous research shown that vascular flow play important role in diffusion-weighted imaging contrast ( Sigmund et al, 2012 ), which means that this study may be biased due to perfusion factors, which require us follow-up further research. Finally, b values selected in this study was similar with the research’s at pons et al (2018) , and there is a slight difference within the b value less than 200. This is because there are no uniform IVIM parameters and quantitative parameters may further improve using abdominal IVIM analysis in animal studies.…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, unpredictable events such as periodic double breaths result in unavoidable corruption of data. In instances where a respiratory triggered approach is considered too inefficient, motion artefacts have been reduced with signal averaging [12]. A variable TR also confounds the quantification of metrics derived from magnetisation preparation schemes such as MT and CEST.…”
Section: Introductionmentioning
confidence: 99%
“…13 IVIM demonstrated excellent corticomedullary differentiation. 12,14 Earlier studies indicated that IVIM parameters were sensitive to chronic renal impairment, such as the grade of clear cell renal cell carcinoma, 15 diabetic kidney, 16,17 ureteral obstruction [18][19][20][21] and renal artery stenosis. 22 The decrease in renal cortical perfusion can explain the alteration in magnetic resonance parameters when renal function changes.…”
Section: Introductionmentioning
confidence: 99%